ENHANCING RESEARCH AND SOCIAL COLLABORATION IN SOUTH ASIA - Malik, Samina (Pakistan Journal of Physiology, 2017)
Physiology is recognized as the mother of Medicine. Research is the doorway to enhance the existing knowledge. The new experiences and discoveries have to be shared with colleagues, seniors and juniors, to disseminate knowledge to those who may benefit from it. Joining professional organizations like the Society for Public Health Education (SOPHE) and attending professional conferences can provide tremendous career development, skill-building, and professional networking opportunities.1 Defining physiological norms in our South Asian population can be one way to take a leap. These normal values are the cutting edge between disease and health. We are bound to follow international norms due to lack of local and regional research. Many great Physiologists are working on establishing the values of Physiological parameters in Pakistani population but there is paucity of publication, presentation and collaboration of research in this field. It is important to collaborate in order to enhance research in Physiology within the country and across the borders on platforms like local Physiological Societies and broader forums like South Asian Association of Physiologists (SAAP)2. Since its inception in Islamabad during the 11th Biennial International Conference of Pakistan Physiological Society3 (PPS-11), the SAAP is regularly hosting its Biennial International Conferences in member countries turn by turn, where local Physiological Societies are well established. This conference is returning to Pakistan, the 2nd time on December 13 to 15, 2018, with Pre-Conference educational workshops on Dec 11 to12 in the historical city of Lahore â€œthe seat of learningâ€ and â€œthe heart of Pakistanâ€. Together, the Physiologists of Pakistan are expected to host, participate and own it, to create a benchmark in the history of South-Asia. This event will bring people, their brains and hearts closer together on a noble cause of teaching and research in Physiology. Representation of vibrant culture by exhibition-booths from all corners of Pakistan will be much appreciated. Sight-seeing, traditional food and musical evening will add colours to this memorable event. SAAPCON 20184 provides an opportunity to collaborate within Pakistan as well as across borders of South Asia. Presentation of such collaborative research will be awarded special prizes in the conference to encourage the Physiologists. Medical & Dental undergraduate, Postgraduate students and Medical Teachers will have the platform of Physiology and Physiologists to exhibit their valuable contributions. It may be followed by publication as a Special Supplement to Pakistan Journal of Physiology5, or in the SAAP Journal that will be launched to disseminate research in SAARC countries (Pakistan, Sri-Lanka, Nepal, Bhutan, Bangladesh, India, and Afghanistan). Pre-conference educational workshops in SAAP conferences are opportunities to learn from and share our experiences with our peers beyond borders. They not only promote mutual learning but also provide opportunity of friendship with our neighbouring colleagues to bring peace, understanding and new perspectives in the region. Representing your Physiology community outside the country on regional platform like SAAP, is an amazing opportunity to express passion for the subject of Physiology. Be the ambassador of your country and culture! By peer-learning across borders, we are able to critically review gaps in our own medical curricula. We are exposed to a variety of research questions in our neighbourhood that broaden our horizons through research collaboration and academic networking. Cultural programs in such conferences bring us closer to our neighbours who share many similarities with our own culture and values. This promotes mutual tolerance and acceptability, which are pre-requisites for the right attitude towards learning. Other than research collaboration, we can initiate exchange of faculty, students and resources among SAAP member countries through its platform. There can be easy access and exposure to Physiology text and reference books published by regional authors as they are frequently displayed at the conference venue. Interaction with scientists across borders and those invited from overseas is another opportunity in such conferences. The direct motivation thus received helps the budding scientists in seeking international research supervisors, who can offer golden shake hand to our undergraduate and postgraduate students. Travelling for learning is such a delightful experience in itself. Be it the low-flight experience over Himalayas in the last SAAP conference2 held in Kathmundu, Nepal or the most amazing ride on cycle rickshaw on the streets of Dhaka, Bangladesh in the second last SAAP conference. Carrying souvenirs on your way back home and tasting cross-cultural food is something to cherish. Looking at our values and culture from the eyes of our regional colleagues and friends, allows for reflection, resulting into personal and national improvement. Let us join hands with SAAP members across borders to promote better research and social understanding in the South Asian region! Pak J Physiol 2017;13(3):1-2